2016
DOI: 10.1016/j.biocel.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy links β-catenin and Smad signaling to promote epithelial-mesenchymal transition via upregulation of integrin linked kinase

Abstract: TGF-β1 induces epithelial-mesenchymal transition (EMT) and autophagy in a variety of cells. However, the role of autophagy in TGF-β1-induced EMT has not been clearly elucidated and the underlying mechanisms are unclear. In the present study, we found that TGF-β1 induced both autophagy and EMT in mouse tubular epithelial C1.1 cells. Inhibition of autophagy by 3-methyladenine or siRNA knockdown of Beclin 1 reduced TGF-β1-induced increase of vimentin and decreased E-cadherin expression. In contrast, rapamycin-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…Focal adhesion disassembly is mediated by autophagy by increased paxillin degradation through either (4a) direct paxillin‐ NBR 1 interaction or (4b) direct paxillin‐ LC 3 interaction upon Src activation . Autophagy upregulation also degrades (5) tight junction proteins (claudin2) and (6) adherens junctions proteins (E‐cadherins) through yet unclarified routes. Autophagy inhibition increases the levels of p62 which stabilize Twist1 in the nucleus to transcriptionally repress E‐cadherin expression .…”
Section: Resultsmentioning
confidence: 99%
“…Focal adhesion disassembly is mediated by autophagy by increased paxillin degradation through either (4a) direct paxillin‐ NBR 1 interaction or (4b) direct paxillin‐ LC 3 interaction upon Src activation . Autophagy upregulation also degrades (5) tight junction proteins (claudin2) and (6) adherens junctions proteins (E‐cadherins) through yet unclarified routes. Autophagy inhibition increases the levels of p62 which stabilize Twist1 in the nucleus to transcriptionally repress E‐cadherin expression .…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is closely related to tumor metastasis, EMT, apoptosis and drug resistance (4951). For instance, autophagy was able to degrade the epithelial marker E-cadherin and promoted EMT of tumors (52,53). Inhibition of autophagy could promote apoptosis of tumor cells (54).…”
Section: Discussionmentioning
confidence: 99%
“…Renal interstitial fibrosis is an inevitable outcome of all causes of progressive chronic kidney disease (CKD). EMT (Pang et al, ), chronic inflammation (Xiao et al, ), oxidative stress (Qin et al, ), and autophagy (Kawaoka et al, ) are reported to be key mechanisms in the pathogenesis and progression of renal interstitial fibrosis. To study renal fibrosis in vivo and in vitro, UUO and TGF‐β‐induced HK‐2 cells are regarded as classical experimental animal and cell models respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Renal interstitial fibrosis is an inevitable outcome of all causes of progressive chronic kidney disease (CKD). EMT (Pang et al, 2016), chronic inflammation (Xiao et al, 2017), oxidative stress (Qin et al, 2016), and autophagy (Kawaoka et al, 2016) are reported to be key mechanisms in the pathogenesis and progression of renal interstitial fibrosis. To study renal fibrosis in vivo and in vitro, UUO and To preliminarily explore which aspects of LncRNA 74.1 exactly exerted its functional role, the markers of inflammation (IL-6, TNF-α, MCP-1), EMT (α-SMA, E-cadherin, and vimentin), oxidative stress resistance (NQO1, HO-1) and autophagy (Atg5, Atg7, and becilin 1) were all detected in LncRNA 74.1 gain-of-function HK-2 cells with or without TGF-β treatment.…”
Section: Discussionmentioning
confidence: 99%